Enhancing Students’ Creative Thinking Skills through Science, Environment, Technology, and Society-Oriented Green Chemistry Entrepreneurship Learning - Mohammad Agus Prayitno; Ulfa Lutfianasari; Deni Ebit Nugroho; Nourma Yulita (Universitas Syiah Kuala, 2026)
Creative thinking skills (CTS) are one of the key competencies projected to be most needed in the next few years. However, various studies have shown that students' CTS are not yet optimal, so learning innovations that are able to integrate concept mastery, problem solving, and creativity development are needed. This study aims to analyze the effectiveness of SETS integration in green chemistry-based entrepreneurship learning (SETS-GCE) on students' CTS. This study uses a quantitative approach with a quasi-experimental one group pretest-postest design. This study uses a total sampling technique involving all members of the population as research samples. Data on CTS were collected through essay tests that measure four aspects, namely fluency, flexibility, originality, and elaboration. Data were analyzed using the Wilcoxon test, normalized gain (N-gain), and effect size. The results showed that SETS-GCE learning significantly improved students' CTS (p <0.05) with a moderate category. The N-gain analysis showed that all aspects of creative thinking skills experienced an increase in the low to moderate category. The elaboration aspect showed the highest increase, while originality showed the lowest increase. These findings indicate that SETS-GCE learning has not been able to optimally enhance originality. Therefore, SETS-GCE implementation needs to be enriched with strategies that explicitly stimulate idea generation, such as brainstorming, design thinking, and open-ended problem solving, to optimally support the development of all aspects of CTS